Faktor-faktor yang Mempengaruhi Kesehatan Jiwa di Lingkungan Kerja - Amelia Susanti; Diana Arianti; Edo Gusdiansyah (Jurnal Ners, 2025)
High workload can increase stress and the risk of mental disorders, while social support and good interpersonal relationships act as protective factors for workers' mental health. This type of research is quantitative with a descriptive correlational approach. This research was conducted in the working area of Puskesmas Kuranji Padang in October 2024 to January 2025.  Population of active workers in Korong Gadang Village, Kuranji Padang Health Center working area. Simple random sampling of 100 respondents. Pearson correlation analysis statistical test. Instruments for workload variables NASA Task Load Index (NASA-TLX). Social Support using the Multidimensional Scale of Perceived Social Support (MSPSS). Interpersonal Relationships using the Interpersonal Relationship Scale (IRS). Mental Health was measured using the General Health Questionnaire (GHQ-12). The results of univariate analysis show Workload: Most respondents experienced moderate workload (52%), respondents received moderate levels of social support (40%), Most respondents had good interpersonal relationships (60%). Bivariate results with Pearson correlation test Workload has a negative correlation with mental health (r = -0.45, p = 0.002). This means that the higher the workload, the higher the risk of mental health disorders in workers. Social support has a positive correlation with mental health (r = 0.50, p = 0.003). This means that the higher the social support workers receive, the better their mental health condition. Interpersonal relationships have a positive correlation with mental health (r = 0.48, p = 0.003), indicating that the better the interpersonal relationships, the lower the risk of mental disorders.